KEPEMIMPINAN DAN ORIENTASI TUJUAN TERHADAP PERILAKU KERJA INOVATIF : TINJAUAN LITERATUR SISTEMATIS - Dheasey Amboningtyas; Leonardo Budi Hasiholan (ITB AAS Indonesia Surakarta, 2026)
Innovative Work Behavior (IWB) has become increasingly important for organizations seeking to enhance innovation and organizational performance. Although previous studies have widely acknowledged the influence of leadership on IWB, existing research remains fragmented in explaining how leadership and goal orientation jointly contribute to innovative work behavior and the mechanisms underlying this relationship. This study aims to systematically synthesize and evaluate the existing literature on leadership, goal orientation, and IWB using the PRISMA-guided Systematic Literature Review (SLR) approach. Approximately 60 peer-reviewed articles indexed in the Scopus database were selected through a structured screening process and analyzed using descriptive and thematic analysis. The findings indicate that the literature is predominantly focused on the direct effects of leadership on IWB, while the integration of goal orientation as a motivational construct and the examination of interaction mechanisms remain limited. The review further identifies communication, collaboration, knowledge sharing, adaptive coordination, and self-regulation as key mechanisms through which leadership influences innovative work behavior. By consolidating fragmented evidence, this review provides an integrated understanding of the relationships among leadership, goal orientation, and IWB, identifies key theoretical gaps, and offers directions for future research.